2004
DOI: 10.1128/jcm.42.1.133-139.2004
|View full text |Cite
|
Sign up to set email alerts
|

Typical Enteroaggregative Escherichia coli Is the Most Prevalent Pathotype among E. coli Strains Causing Diarrhea in Mongolian Children

Abstract: Diarrhea remains one of the main sources of morbidity and mortality in the world, and a large proportion is caused by diarrheagenic Escherichia coli. In Mongolia, the epidemiology of diarrheagenic E. coli has not been well studied. A total of 238 E. coli strains from children with sporadic diarrhea and 278 E. coli strains from healthy children were examined by PCR for 10 virulence genes: enteropathogenic E. coli (EPEC) eae, tir, and bfpA; enterotoxigenic E. coli (ETEC) lt and st; enteroinvasive E. coli (EIEC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
122
5
15

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(160 citation statements)
references
References 45 publications
18
122
5
15
Order By: Relevance
“…A recent study from Libya found similar results, with multivirulence being detected in 50% of EAEC from diarrheic children [26]. Sarantuya et al reported a lower rate (< 30%) of multivirulence among EAEC from children with diarrhea in Mongolia [32].…”
Section: Discussionsupporting
confidence: 60%
“…A recent study from Libya found similar results, with multivirulence being detected in 50% of EAEC from diarrheic children [26]. Sarantuya et al reported a lower rate (< 30%) of multivirulence among EAEC from children with diarrhea in Mongolia [32].…”
Section: Discussionsupporting
confidence: 60%
“…In the present study 35.2 % isolates did not produce any quantifiable biofilm although all the strains were aggR positive. This corroborates with the findings of other workers [17,20] who also observed no correlation between aggR and biofilm formation. However, Mohamed et al [12] observed that isolates carrying aggR alone or in combination with other virulence genes were strongly associated with biofilm formation.…”
Section: Discussionsupporting
confidence: 83%
“…47 We found three or more virulence genes (multivirulent isolates) in 50% of EAEC isolates. Sarantuya and others 48 reported multivirulence in 30% of EAEC from diarrheic children in Mongolia. A study from Brazil examined EAEC from diarrheic and control children for 11 virulence markers and found multivirulence in 74% of EAEC strains.…”
Section: Discussionmentioning
confidence: 99%
“…Results of this study show an abundance of typical rather than atypical EAEC among diarrheic Libyan children, as reported elsewhere. 47,48 Previous studies have reported that astA (EAST1) is not restricted to EAEC isolates and is significantly associated with diarrhea. 49,50 Furthermore it has been observed that, in addition to toxin EAST1, pet (Pet) seems to be common in the E. coli population and not restricted to EAEC.…”
Section: Discussionmentioning
confidence: 99%